A Systematic Review on The Insurability Risk for Long-Term Care Insurance in Europe and Asia Countries - Nurin Amni Arshad; Mazlynda Md Yusuf (Penerbit USIM, Universiti Sains Islam Malaysia, 2024)
E-Proceeding Kolokium Siswazah Fakulti Sains Dan Teknologi 2020 (KOSIST 2020) “Synergizing Innovation and Research Through Science and Technology” 9th December 2020 Organized by Faculty Science and Technology